catena-Poly[lead(II)-bis(μ(2)-pyridazine-3-carboxylato-κ(3) N (2),O:O)] - Starosta, Wojciech (International Union of Crystallography, 2010)
In the title structure, [Pb(C(5)H(3)N(2)O(2))(2)](n), the Pb(II) ion is six-coordinated by two pyridazine-3-carboxylate ligands via N and O atoms, with the carboxylato O atoms acting as bidentate and bridging adjacent Pb(II) ions, giving rise to catenated molecular ribbons propagating along the a-axis direction. The ribbons are connected by C—H⋯O hydrogen bonds and van der Waals interactions.